Strategi Meningkatkan Efektivitas Organisasi Melalui Training Komunikasi Asertif - Rahmah, Dian Dwi Nur; Prastika, Netty Dyan; Windarti, Baiq; Agsari, Eka Juliyana; Firjatullah, Firjatullah (Universitas Pahlawan Tuanku Tambusai, 2025)
Good communication skills within an organization are key to success in achieving goals. One factor that can influence the smoothness of communication within an organization is assertive communication. This study aims to evaluate the impact of assertive communication training on the effectiveness of the Indonesian Islamic Student Movement (PMII) branch in Kutai Kartanegara. The research employs the experimental learning method, which includes Training Need Analysis (TNA), module development, implementation using experiential learning, and evaluation. The assessment is conducted to measure participants' cognitive improvements and their reactions to the training. Assertive communication training for effective organizational communication was conducted for 34 participants in the PMII branch in Kutai Kartanegara. The results indicate cognitive improvement from pre-test to post-test, although statistical significance was not observed with a significance level of (2-tailed) = 0.714 > 0.05. Nevertheless, participants' reactions to the training suggest positive outcomes. The facilitator evaluation graph and training implementation also highlight the positive impact of assertive communication within the organization.